2016
DOI: 10.1073/pnas.1419248113
|View full text |Cite
|
Sign up to set email alerts
|

Chimera proteins with affinity for membranes and microtubule tips polarize in the membrane of fission yeast cells

Abstract: Cell polarity refers to a functional spatial organization of proteins that is crucial for the control of essential cellular processes such as growth and division. To establish polarity, cells rely on elaborate regulation networks that control the distribution of proteins at the cell membrane. In fission yeast cells, a microtubule-dependent network has been identified that polarizes the distribution of signaling proteins that restricts growth to cell ends and targets the cytokinetic machinery to the middle of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…Stronger oligomerization reduces the rate at which local asymmetries grow, and the rate at which they approach steady state. This allows external cues that promote local binding [14, 17, 46, 47] or unbinding [48] of polarity factors, or their rapid transport by actomyosin flows [18, 19, 44] to impose spatial asymmetry patterns that are then maintained as quasi-stable states over much longer timescales, and which are no longer dictated by the internal reaction/diffusion kinetics of the polarity circuit. While increasing oligomerization strength to maintain asymmetries far from steady state will also necessarily decrease the rate at which asymmetries grow, this can be readily overcome through the rapid control of local binding/unbinding or transport by external inputs.…”
Section: Discussionmentioning
confidence: 99%
“…Stronger oligomerization reduces the rate at which local asymmetries grow, and the rate at which they approach steady state. This allows external cues that promote local binding [14, 17, 46, 47] or unbinding [48] of polarity factors, or their rapid transport by actomyosin flows [18, 19, 44] to impose spatial asymmetry patterns that are then maintained as quasi-stable states over much longer timescales, and which are no longer dictated by the internal reaction/diffusion kinetics of the polarity circuit. While increasing oligomerization strength to maintain asymmetries far from steady state will also necessarily decrease the rate at which asymmetries grow, this can be readily overcome through the rapid control of local binding/unbinding or transport by external inputs.…”
Section: Discussionmentioning
confidence: 99%
“…The role of MT-mediated transport in maintaining cell polarity is well established in fission yeast, where the polarity factors Tea1/Tea4 are transported through association with MT plus-end tracking (+TIPs) proteins such as Mal3 and the kinesin Tea2 to ensure the polar localization of cell growth [ 32 ]. Recently, Recouvreuz et al [ 33 ] have “deconstructed” this system, by using a explicitly engineered chimeric complex using the membrane binding domain of Pom1 coupled to Mal3. This minimal system also displays clear polar enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…As Mod5 presence at the sides of the cell is very low, transfers there are less probable [Minc et al 2000, Snaith andSawin 2003]. We previously showed that an artificial cortical protein that is able to diffuse can form a polarized distribution simply by interactions with microtubule tips in S. pombe [Recouvreux et al 2016]. Therefore, motile receptors, with direct or indirect microtubule binding may facilitate restricting transfers to the poles of the cell.…”
Section: Polarity Establishmentmentioning
confidence: 99%